Le post-multiculturalisme de David Cameron - Didier Lassalle (Revue Française de Civilisation Britannique)
There is an obvious link between the policies developed by the New Labour governments as regards ethnic minorities’ integration and immigration control after 2001 and the new set of policies recently introduced by David Cameron’s coalition government: in particular, the rejection of multiculturalism and the return to a more traditional view of integration. However, several specific trends can be underlined. First, the previous policies based on “identity politics” have been radically challenged and replaced by a new “strategy for equality”. Second, the government wants to force the British system of values on the newcomers in order to restore a minimum of cultural homogeneity, which marks the revival of the concept of assimilation abandoned in the mid-1960s. Finally, the continuous and severe stigmatization of Islam and of Muslims has become a worrying tendency which increases the ‘community divide’ that David Cameron adamantly denounced when he was the leader of the opposition.